Interfaces Mobile: metodologia de desenvolvimento de modelos de navegação e análise de inadequação de heranças da comunicação analógica - Constantino, Juliana Maria (2008)
Diversity and popularization of the wireless equipment used for telephony, listening to music and personal organization are grabbing attention to these mobile devices. The low prices, especially of mobile phones, require a critical study of their interfaces, as it has became one of the cores of contemporary communication. The goal of this research is to investigate models of navigation adopted by products that access the Internet, developed for portable devices - be it web sites, or applications - with focus on the complexity of the communication system involved in this context and the methodology of development of these interfaces. The survey was conducted from a site developed for the launch of a product's auto industry, whose presence on-line started with a website exclusively "mobile" in August 2007. In this analysis, were considered: the launch of the car, study of public and habits of interaction with mobile services, creative strategy, information architecture / general guidelines of the interface and result. It was also part of the analysis the behavior of guidelines for interface in popular cel phones (low-cost) and in multifunctional models like multimedia phones, smartphones or the iPhone, considering the the heterogeneous Brazilian cellphone base (in terms of technical capability of equipment and plans pre and post-paid), which reflects the relationship among holder-interaction-network. The theoretical North of the research was " Towards a Philosophy of Photography " by Vilém Flusser and all the discussion happened in the light of the latest literature on the information architecture, design, interface and communication theory's post-media: Lev Manovich, William Mitchell , Manuel Castells, Andre Lemos, Giselle Beiguelman and Lucia Santaella, among other no less important. The analysis resulted in a critical view on the situations of use of different features of wireless devices, focusing mainly in the creative process involved on the construction of such interfaces - considering legacies of the fixed Internet - and the relationship between public and equipment